A Natural Allele of a Transcription Factor in Rice Confers Broad-Spectrum Blast Resistance - Li, Weitao; Zhu, Ziwei; Chern, Mawsheng; Yin, Junjie; Yang, Chao; Ran, Li; Cheng, Mengping; He, Min; Wang, Kang; Wang, Jing; Zhou, Xiaogang; Zhu, Xiaobo; et al. (Cell, 2017)
Rice feeds half the world’s population, and rice blast is often a destructive disease that results in significant crop loss. Non-race-specific resistance has been more effective in controlling crop diseases than race-specific resistance because of its broad spectrum and durability. Through a genome-wide association study, we report the identification of a natural allele of a C2H2-type transcription factor in rice that confers non-race-specific resistance to blast. A survey of 3,000 sequenced rice genomes reveals that this allele exists in 10% of rice, suggesting that this favorable trait has been selected through breeding. This allele causes a single nucleotide change in the promoter of the bsr-d1 gene, which results in reduced expression of the gene through the binding of the repressive MYB transcription factor and, consequently, an inhibition of H2O2 degradation and enhanced disease resistance. Our discovery highlights this novel allele as a strategy for breeding durable resistance in rice. [Display omitted] •A single base change (SNP33-G) in the bsr-d1 promoter enhances binding to MYBS1•Binding of MYBS1 to the bsr-d1 promoter suppresses bsr-d1 expression•BSR-D1 promotes peroxidase expression, suppressing immunity to M. oryzae•The SNP33-G allele is present in 10% of 3,000 surveyed rice varieties A natural allele of a C2H2-domain transcription factor gene, bsr-d1, confers broad-spectrum resistance to rice blast.